Rationing without government: the West Coast gas famine of 1920 - Olmstead, Alan L.; Rhode, Paul W. (American Economic Review, 1985)
Arguing that the beliefs that there were no energy shortages in the US before the 1970s and that large-scale rationing requires government price controls are clearly wrong, the authors analyze the extent of the shortage, the nature of the rationing program, and the structure of the petroleum industry. They argue that regional isolation, industry concentration, and the vertical integration of the larger firms made rationing possible. In the absence of laws requiring rationing or setting prices, they focus on the hypothesis that the oil companies held prices down because they were afraid of hostile government actions. 22 references, 2 figures, 1 table.